Hypersensitivity of Ku-Deficient Cells toward the DNA Topoisomerase II Inhibitor ICRF-193 Suggests a Novel Role for Ku Antigen during the G(2) and M Phases of the Cell Cycle - Muñoz, Purificación (American Society for Microbiology (ASM), 1998)
Ku antigen is a heterodimer, comprised of 86- and 70-kDa subunits, which binds preferentially to free DNA ends. Ku is associated with a catalytic subunit of 450 kDa in the DNA-dependent protein kinase (DNA-PK), which plays a crucial role in DNA double-strand break (DSB) repair and V(D)J recombination of immunoglobulin and T-cell receptor genes. We now demonstrate that Ku86 (86-kDa subunit)-deficient Chinese hamster cell lines are hypersensitive to ICRF-193, a DNA topoisomerase II inhibitor that does not produce DSB in DNA. Mutant cells were blocked in G(2) at drug doses which had no effect on wild-type cells. Moreover, bypass of this G(2) block by caffeine revealed defective chromosome condensation in Ku86-deficient cells. The hypersensitivity of Ku86-deficient cells toward ICRF-193 was not due to impaired in vitro decatenation activity or altered levels of DNA topoisomerase IIα or -β. Rather, wild-type sensitivity was restored by transfection of a Ku86 expression plasmid into mutant cells. In contrast to cells deficient in the Ku86 subunit of DNA-PK, cells deficient in the catalytic subunit of the enzyme neither accumulated in G(2)/M nor displayed defective chromosome condensation at lower doses of ICRF-193 compared to wild-type cells. Our data suggests a novel role for Ku antigen in the G(2) and M phases of the cell cycle, a role that is not related to its role in DNA-PK-dependent DNA repair.